Pengaruh Inovasi Layanan dan Kualitas Produk Terhadap Loyalitas Pelanggan pada Pelanggan Provider XL AXIATA di Sidoarjo - Nadia Putri Prasetianto; Rusdi Hidayat Nugroho (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
A company can enhance customer satisfaction, which ultimately leads to customer loyalty, by consistently providing excellent services and innovations. Customer satisfaction can be achieved through the innovations and services offered by the company, as well as through the quality of its products, which foster customer trust and loyalty. This study aims to examine the influence of service innovation and product quality on customer loyalty, both partially and simultaneously, among XL provider customers in Sidoarjo. This research uses a quantitative method with data collection through questionnaires. The population consists of all XL provider customers in Sidoarjo, totaling 135 people. The sampling technique used is simple random sampling, resulting in 57 respondents as the sample. Data analysis techniques include instrument testing, classical assumption tests, and hypothesis testing. The results show that: (1) the service innovation variable has a t-value of 7.417 > t-table value of 1.67203, with a significance level of 0.000 < 0.05, indicating a positive and significant partial influence on customer loyalty; (2) the product quality variable has a t-value of 2.825 > 1.67203 and a significance level of 0.007 < 0.05, also indicating a positive and significant partial influence on customer loyalty; and (3) simultaneously, service innovation and product quality have a significant effect on customer loyalty, as evidenced by an F-value of 77.762 > F-table value of 2.77 and a significance level of 0.000 < 0.05.